2020
DOI: 10.1590/0074-02760190423
|View full text |Cite
|
Sign up to set email alerts
|

Genomic detection of a virus lineage replacement event of dengue virus serotype 2 in Brazil, 2019

Abstract: BACKGROUND Despite efforts to mitigate the impact of dengue virus (DENV) epidemics, the virus remains a public health problem in tropical and subtropical regions around the world. Most DENV cases in the Americas between January and July 2019 were reported in Brazil. São Paulo State in the southeast of Brazil has reported nearly half of all DENV infections in the country. OBJECTIVES To understand the origin and dynamics of the 2019 DENV outbreak. METHODS Here using portable nanopore sequencing we generated20 ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
33
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 26 publications
7
33
0
3
Order By: Relevance
“…To uncover the origins of the recent dengue outbreaks, we combined our 46 DENV-1 and 23 DENV-2 genomes with others that were available (see Methods), and inferred time-resolved phylogenetic trees (DENV-1 = 200 total genomes, Figure 4; DENV-2 = 220 total genomes, Figure 5; root-to-tip estimates of evolutionary rate, Figure S6). Our data show that the time to most recent common ancestor (tMRCA) DENV-1 viruses sequenced from Paraíba and Alagoas was mid-2012 (95% Bayesian credible interval (BCI) 2011.79-2013.33; Figure 4), and the tMRCA for DENV-2 viruses sequenced from São Paulo was early 2014 (95% BCI 2013.33-2014.61; Figure 5), which was independently confirmed 40 . As there are far more available DENV envelope protein coding sequences than whole genomes [41][42][43] , we repeated our analysis using 1250 DENV-1 ( Figure S7) and 1202 DENV-2 ( Figure S8) envelope sequences reported in previous studies [41][42][43] , and we found similar clustering patterns and ancestral phylogeographic origins.…”
Section: Virus Genomics Reveals the Timing Of The Denv Outbreak Lineagessupporting
confidence: 62%
“…To uncover the origins of the recent dengue outbreaks, we combined our 46 DENV-1 and 23 DENV-2 genomes with others that were available (see Methods), and inferred time-resolved phylogenetic trees (DENV-1 = 200 total genomes, Figure 4; DENV-2 = 220 total genomes, Figure 5; root-to-tip estimates of evolutionary rate, Figure S6). Our data show that the time to most recent common ancestor (tMRCA) DENV-1 viruses sequenced from Paraíba and Alagoas was mid-2012 (95% Bayesian credible interval (BCI) 2011.79-2013.33; Figure 4), and the tMRCA for DENV-2 viruses sequenced from São Paulo was early 2014 (95% BCI 2013.33-2014.61; Figure 5), which was independently confirmed 40 . As there are far more available DENV envelope protein coding sequences than whole genomes [41][42][43] , we repeated our analysis using 1250 DENV-1 ( Figure S7) and 1202 DENV-2 ( Figure S8) envelope sequences reported in previous studies [41][42][43] , and we found similar clustering patterns and ancestral phylogeographic origins.…”
Section: Virus Genomics Reveals the Timing Of The Denv Outbreak Lineagessupporting
confidence: 62%
“…This phylogenetic pattern suggests that between 2016 and 2019 DENV2 circulated in these Brazilian regions with a succession of different viral clades from to BR-3 and then BR-4, with older clades (BR-1, BR-2) either not being sampled in the most recent time-points or having experienced local extinction. These phylogenetic results are consistent with a recent study highlighting the role of the Caribbean region in the spread of the BR-4 clade into Brazil 29,33 (Figure 3 panel A).…”
Section: Resultssupporting
confidence: 93%
“…This analysis revealed four different clades (termed hereafter BR-1 to BR-4 clades). 33 Notably, BR-1 contained Brazilian sequences sampled from 1990-2000 BR-2 from 2000-2006, and BR-3 from 2006-2019. The latter included six of our new isolates (3·5%, 6/170) collected during previous outbreaks in 2008 (GO=3) and 2016 (SP=3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, all of this cohort’s specimens corresponded to genotype III (formerly known as Asian/American), which is circulating in Brazil since its introduction in 1988–1989. However, samples grouped within two different clusters with 100% bootstrap supported ( Figure 1 ) Brazilian lineage BR3, which corresponded to viral strains circulating after DENV-2 re-introduction in the state of Rio de Janeiro in 2007, and the newly described lineage BR4, which included strains circulating in the country since 2016 [ 41 , 42 ]. Even though BR4 might be a new lineage spreading through Brazil, their representing sequences still grouped within the clade IV of genotype III and was not as genetically diverse from BR3.…”
Section: Resultsmentioning
confidence: 99%